Childhood bladder and bowel dysfunction predicts irritable bowel syndrome phenotype in adult interstitial cystitis/bladder pain syndrome patients - Doiron, R. Christopher; Kogan, Barry A.; Tolls, Victoria; Irvine-Bird, Karen; Nickel, J. Curtis (Canadian Urological Association Journal, 2017)
Introduction: Many clinicians have suggested that a history of bladder and bowel dysfunction (BBD) in childhood predisposes to the development of interstitial cystitis/bladder pain syndrome (IC/BPS) or irritable bowel syndrome (IBS) in adulthood. We hypothesized that BBD symptoms in childhood would predict the IBS-associated phenotype in adult IC/BPS patients. Methods: Consecutive female patients (n=190) with a diagnosis of IC/BPS were administered a modified form of a clinical BBD questionnaire (BBDQ) to capture childhood BBD-like symptoms, as well as Interstitial Cystitis Symptoms Index (ICSI), Interstitial Cystitis Problem Index (ICPI), Pelvic Pain and Urgency/ Frequency (PUF) questionnaires and UPOINT categorization. Patients were stratified to IBS-positive or IBS-negative according to clinical assessment of IBS-like symptoms. Results: The 127 patients (67%) identified with IBS-like symptoms recalled significantly higher BBDQ scores than the 63 patients (33%) who were IBS-negative (2.8 vs. 2.3; p=0.05). The IBS-positive patients also reported a higher number of UPOINT domains than their non-IBS counterparts (3.8 vs. 2.9; p=0.0001), while their PUF total scores were significantly higher (13.6 vs. 12.3; p=0.04). IBSpositive patients more often recalled that in childhood they did not have a daily bowel movement (BM) (p=0.04) and had “to push for a BM” (p=0.009). In childhood, they “urinated only once or twice per day” (p=0.03) and recalled “painful urination” more than those without IBS (p=0.03). There were no significant differences between the groups in answers to the other five questions of the BBDQ. Conclusions: Our symptom recollection survey was able to predict the IBS phenotype of IC/BPS based on a childhood BBDQ. Further prospective studies are needed to further evaluate these novel findings.